A relação das habilidades do processamento auditivo com a consciência fonológica e com o desenvolvimento da fala - Quintas, Victor Gandra (2009)
This study aimed to verify the relationship between the auditory processing with the phonology and the phonological awareness in monolingual Brazilian Portuguese speaking children. The study had the participation of subjects with both normal phonological development and deviant. In the children with deviations, it sought to identify the involvement of processing skills with distinctive combinations of acquired and changed features. The research involved a total of 44 subjects, who were divided equally into the control and the study group. Their ages ranged from 5 to 7 years old and all of them were right-handed. The diagnosis of phonological disorder was determined by speech-language evaluations and complementary exams. The Protocol of Phonological Awareness Tasks (PPAT), proposed by Cielo (2001), as well as the Simplified Evaluation of Auditory Processing and the special tests - Test PSI in Portuguese; Binaural Fusion Test (BFT); Speech-in-noise Test (SPN); Dichotic Digit Test; and Staggered Spondaic Word Test (SSW) from Central Auditory Processing: Application Manual, proposed by Pereira and Schochat (1997). In subjects with phonological disorder, it was still considered the combination of distinctive features through the Implicational Model of Features Complexity (MICT), written by Mota (1996), as well as it was calculated the Percentage of Consonants Correct-Revised (PCC-R) by Shriberg et al. (1997). The obtained results in general showed that the group with phonological deviations has lower results in auditory processing and phonological awareness than the group who had typical speech acquisition. The phonological awareness in relation to auditory processing may not be outdated in both groups. In terms of distinctive features and their combinations, according to the MICT, we should note that some listening skills, especially the temporal ordering can be correlated; however, no statistically significant results could be observed. So, it is believed that the small sample might have affected the values. Finally, we conclude that there is a close relationship between the hearing process with the speech acquisition, either as a regular or as a deviant form. Thus, further studies can help develop this area still poorly developed.